2014
DOI: 10.1097/aci.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells in asthma

Abstract: Although the limited success of these trials is often quoted to dismiss the role of Th2 immunity as a whole, we propose that Th2 cytokines released by ILC2s may be critical for human asthma, but are not adequately neutralized because they are not readily accessible in peripheral tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Schuster et al also demonstrated in an airway inflammation model that n-3 PUFAs had a tendency to increase IL-5 secretion [23]. It is important to note that IL-5 is implicated in the pathogenesis of several diseases, particularly lung inflammatory conditions such as asthma [24]. The findings from this study and others imply that an enhancement in IL-5 secretion in humans could have negative consequences for inflammatory lung diseases.…”
Section: Discussionsupporting
confidence: 57%
“…Schuster et al also demonstrated in an airway inflammation model that n-3 PUFAs had a tendency to increase IL-5 secretion [23]. It is important to note that IL-5 is implicated in the pathogenesis of several diseases, particularly lung inflammatory conditions such as asthma [24]. The findings from this study and others imply that an enhancement in IL-5 secretion in humans could have negative consequences for inflammatory lung diseases.…”
Section: Discussionsupporting
confidence: 57%
“…TSLP activates dendritic cells 9 and also directly promotes naive CD4 + T cells to into type 2 helper T cells (Th2 cells) 10 . IL-25, IL-33, and TSLP can stimulate group 2 innate lymphoid cells (ILC2) to release type 2 cytokines 11 14 . IL-25 15 18 , IL-33 19 , and TSLP 10 have each been reported to be both necessary and sufficient for type 2 production, eosinophilic airway inflammation, mucous metaplasia, and airway hyperresponsiveness in mouse asthma models.…”
Section: Introductionmentioning
confidence: 99%
“…Innate Lymphoid Cells Innate lymphoid cells (ILCs) are non-T, non-B effector cells that show high levels of effector cell functions (mainly cytokine production) upon activation [106]. ILCs are involved in tissue homeostasis, repair, and remodeling, as well as innate immunity [107].…”
Section: Fungal Asthma-associated Inflammationmentioning
confidence: 99%